Functionalised mesoporous silica membrane for the separation of carbon dioxide. (1st September 2004) - Kim, Sangil; Ida, Junichi; Guliants, Vadim V.; Lin, Y. S.
Defect-free mesoporous silica membranes (MCM-41 and MCM-48) were obtained by spin-coating and the solution growth method; 3-aminopropylsilyl groups were attached to the surface of these silica membranes. The pore size control in these novel silica membranes was achieved by direct synthesis employing cationic surfactants and post-synthesis silylation procedure using silane coupling agents. The SEM and unsteady-state gas permeation studies using He and CO2 indicated the absence of "pinhole" defects in mesoporous silica membranes. The presence and surface concentration of the amino groups in the silica membrane upon attachment was studied by the IR spectroscopy, elemental analysis and TGA, which confirmed the high surface concentration of amino groups in the silica membrane.